Tyrosine hydroxylase activity in the endocrine pancreas: changes induced by short-term dietary manipulation - Gagliardino Juan J; Flores Luis E; García María E; Rubio Modesto; Borelli María I (BMC Endocrine Disorders, 2003)
Abstract Background Tyrosine hydroxylase (TH) activity and its possible participation in the control of insulin secretion were studied in pancreatic islets of adult Wistar rats fed a standard commercial diet (SD) or carbohydrates alone (CHD) for one week. TH activity, norepinephrine (NE) content, and glucose-induced insulin secretion were assessed. Blood glucose and insulin levels were measured at the time of sacrifice. Results CHD rats had significantly higher blood glucose and lower insulin levels than SD rats (114.5 ± 6.7 vs 80.7 ± 7.25 mg/dl, p < 0.001; 20.25 ± 2.45 vs 42.5 ± 4.99 μU/ml, p < 0.01, respectively). Whereas TH activity was significantly higher in CHD isolated islets (600 ± 60 vs 330 ± 40 pmol/mg protein/h; p < 0.001), NE content was significantly lower (18 ± 1 vs 31 ± 5 pmol/mg protein), suggesting that TH activity would be inhibited by the end-products of catecholamines (CAs) biosynthetic pathway. A similar TH activity was found in control and solarectomized rats (330 ± 40 vs 300 ± 80 pmol/mg protein/h), suggesting an endogenous rather than a neural origin of TH activity. CHD islets released significantly less insulin in response to glucose than SD islets (7.4 ± 0.9 vs 11.4 ± 1.1 ng/islet/h; p < 0.02). Conclusions TH activity is present in islet cells; dietary manipulation simultaneously induces an increase in this activity together with a decrease in glucose-induced insulin secretion in rat islets. TH activity – and the consequent endogenous CAs turnover – would participate in the paracrine control of insulin secretion.